2016
DOI: 10.3390/jdb4020016
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Specificity for Hox Factor Activity

Abstract: Metazoans encode clusters of paralogous Hox genes that are critical for proper development of the body plan. However, there are a number of unresolved issues regarding how paralogous Hox factors achieve specificity to control distinct cell fates. First, how do Hox paralogs, which have very similar DNA binding preferences in vitro, drive different transcriptional programs in vivo? Second, the number of potential Hox binding sites within the genome is vast compared to the number of sites bound. Hence, what deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 150 publications
(260 reference statements)
0
22
0
Order By: Relevance
“…Their differential expression along the main body axis establishes positional information that instructs cells about their fate, ultimately generating morphological diversity [1][2][3] . The wide-range of HOX-dependent genetic programs is intriguing considering that the various HOX TFs have similar DNA-binding properties 6 . Several studies uncovered the relevance of co-factors, notably the PBX/Exd family of TFs, in increasing DNAbinding specificity [4][5][6] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Their differential expression along the main body axis establishes positional information that instructs cells about their fate, ultimately generating morphological diversity [1][2][3] . The wide-range of HOX-dependent genetic programs is intriguing considering that the various HOX TFs have similar DNA-binding properties 6 . Several studies uncovered the relevance of co-factors, notably the PBX/Exd family of TFs, in increasing DNAbinding specificity [4][5][6] .…”
mentioning
confidence: 99%
“…The wide-range of HOX-dependent genetic programs is intriguing considering that the various HOX TFs have similar DNA-binding properties 6 . Several studies uncovered the relevance of co-factors, notably the PBX/Exd family of TFs, in increasing DNAbinding specificity [4][5][6] . Analyses using micromass culture from primary mesenchymal limb bud cells revealed that group 11 and 13 Hox genes cluster in the same subgroup 10 despite the fact that HOXA11/HOXD11 are required for the zeugopod (forearm) developmental program 11 while HOXA13 and HOXD13 are mandatory for digit development 12 (Fig.…”
mentioning
confidence: 99%
“…A long-standing question in developmental biology has been how homologous transcription factors with similar DNA binding domains produce different activities. The Hox homeodomain factors are exemplars of such protein families, as each Hox factor binds similar AT-rich sequences in vitro, yet drives distinct developmental programs in vivo [7]. One advance in answering this paradox was to show that Hox proteins have different binding preferences in the presence of Exd and Hth [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…While the number of Hox genes varies between animals, Hox genes share in common the property of instructing cells to adopt a "regional" (or "segment") identity within the organism by regulating the expression of downstream target genes [3]. Recent genomic studies have indicated Hox factors affect the expression of hundreds of downstream target genes [4][5][6][7]. Since each region or segment under the control of a specific Hox factor is composed of many cell-and tissue-types, these findings present two fundamental challenges in understanding how Hox genes sculpt the body plan: First, what makes one Hox factor different from another to specify distinct embryonic regions during development?…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Drosophila, the phosphorylation state of the HOX protein is crucial for its transcriptional activity (Berry & Gehring, 2000). In addition, the presence of the co-factors that modulate transcriptional activity of Drosophila HOX was reported (reviewed in Zandvakili & Gebelein, 2016). Since these mechanisms related to HOXA13 have yet to be elucidated, research into this issue will be a topic for future studies.…”
Section: Hox13 Regulates Cartilage Differentiation In a Dual Mannermentioning
confidence: 99%